2006
DOI: 10.1088/0957-4484/17/3/006
|View full text |Cite
|
Sign up to set email alerts
|

One-step formation of nanostructured gold layers via a galvanic exchange reaction for surface enhancement Raman scattering

Abstract: Gold films with various nanostructures on porous silicon substrates have been created in one step by using a galvanic exchange reaction approach. In this approach, the formation of gold films is initiated by the formation of metal nuclei via an exchange reaction in which both the oxidation of silicon and reduction of gold complex occur simultaneously. Results show that the deposition of gold film is diffusion controlled, and its apparent activation energy was determined to be 28.57 kJ mol−1. Therefore, gold na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…In the case of the work of Xia et al, silver particles formed are used as the "template" and gold ions are added to the solution. [60][61][62] Because the standard reduction potential of the AuCl 4 − -Au pair (0.99 V, vs SHE) is higher than that of the Ag + -Ag pair (0.80 V vs SHE), gold ions are reduced at the surface of Ag nanoparticles, and silver metal will be oxidized into Ag + ions. One salient feature is that this approach can be applied to almost any shapes of nanostructures such as hollow rods, spheres, rattles, cubes, and wires.…”
Section: Synthesismentioning
confidence: 99%
“…In the case of the work of Xia et al, silver particles formed are used as the "template" and gold ions are added to the solution. [60][61][62] Because the standard reduction potential of the AuCl 4 − -Au pair (0.99 V, vs SHE) is higher than that of the Ag + -Ag pair (0.80 V vs SHE), gold ions are reduced at the surface of Ag nanoparticles, and silver metal will be oxidized into Ag + ions. One salient feature is that this approach can be applied to almost any shapes of nanostructures such as hollow rods, spheres, rattles, cubes, and wires.…”
Section: Synthesismentioning
confidence: 99%
“…The galvanic reaction is reported to be very effective and reproducible for preparing various metallic nanostructures with applications in catalysis and as SERS substrates. 1924 …”
Section: Introductionmentioning
confidence: 99%
“…24 They showed that the plasmon resonance peak can be continuously tailored by controlling the total length of the nano-chain, but their study didn't provide the actual realization of SERS effect. A SERS effect was demonstrated from a 3-D dendrite structure 25 and it was found that a dendrite structure with leaf-like branches exhibits the strongest enhancement against the ordered and compacted text and dendrite structures, in agreement with the fact that the increase of surface roughness should improve the enhancement. However, the molar concentration of probe molecules was too high for such an enhancement to be solely accounted for by SERS effect and the reproducibility of the SERS data from different spots was not carefully examined.…”
Section: Resultsmentioning
confidence: 60%